Incidence of familial tendon dysfunction in patients with full-thickness rotator cuff tears - Tashjian RZ; Saltzman EG; Granger EK; Hung M (Dove Medical Press, 2014)
Robert Z Tashjian, Erik G Saltzman, Erin K Granger, Man Hung Department of Orthopedics, University of Utah Orthopaedic Center, University of Utah School of Medicine, Salt Lake City, UT, USA Background: A familial predisposition to the development of rotator cuff tearing has been previously reported. Very little information exists on the development of global tendon dysfunction in patients with rotator cuff tears. The purpose of the current study was to determine the incidence of global tendon dysfunction as well as the need for surgery for tendon dysfunction in patients with rotator cuff tears and their family members and compare them to age-matched controls. Methods: Ninety two patients with full-thickness rotator cuff tears and 92 age-matched controls with no history of shoulder dysfunction or surgery responded to several questions regarding tendon diseases in themselves as well as their family members. Individuals were queried regarding the presence of tendon diseases other than the rotator cuff, the need for surgery on these other tendinopathies, the presence of family members having tendinopathies including rotator cuff disease, and the need for family members to have surgery for these problems. Chi-square analysis was performed to compare the incidences between cases and controls (P<0.05 was considered significant). Results: The average age of patients in the rotator cuff tear group and control groups were 58.24±7.4 and 58.42±8.5 years, respectively (P=0.876). Results showed 32.3% of patients in the rotator cuff tear group reported that family members had a history of rotator cuff problems or surgery compared to only 18.3% of the controls (P=0.035), and 38.7% of patients in the rotator cuff tear group reported they had a history of other tendon problems compared to only 19.3% of individuals in the control group (P=0.005). Conclusion: Individuals with rotator cuff tears report a higher incidence of family members having rotator cuff problems or surgery as well as a higher incidence of other tendinopathies compared to controls. This data further supports a familial predilection for the development of rotator cuff tearing and generalized tendinopathies. Keywords: family history, tendinopathies